2019
DOI: 10.1093/ajcn/nqy220
|View full text |Cite
|
Sign up to set email alerts
|

Complementary feeding and food allergy, atopic dermatitis/eczema, asthma, and allergic rhinitis: a systematic review

Abstract: Background Nutrition during infancy and toddlerhood may influence health and disease prevention across the life span. Complementary feeding (CF) starts when human milk or infant formula is complemented by other foods and beverages, beginning during infancy and continuing to age 24 mo. Objectives The aim of this study was to describe systematic reviews conducted for the USDA and the Department of Health and Human Services Preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 71 publications
0
55
0
1
Order By: Relevance
“…EFSA staff hand‐searched through the bibliography of: −the studies included from all the searches described above, −the systematic reviews (those performed by USDA (English et al., , English et al., ; Obbagy et al., ; Obbagy et al., ; Obbagy et al., ) and published shortly before the launch of the public consultation on this Scientific Opinion were searched during the public consultation and relevant papers were added thereafter), −the theses found through the search of grey literature undertaken by the external contractor. …”
Section: Data and Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…EFSA staff hand‐searched through the bibliography of: −the studies included from all the searches described above, −the systematic reviews (those performed by USDA (English et al., , English et al., ; Obbagy et al., ; Obbagy et al., ; Obbagy et al., ) and published shortly before the launch of the public consultation on this Scientific Opinion were searched during the public consultation and relevant papers were added thereafter), −the theses found through the search of grey literature undertaken by the external contractor. …”
Section: Data and Methodologiesmentioning
confidence: 99%
“…For outcomes on atopic diseases, Obbagy et al. () reported that there was moderate evidence for no association between the age of CF introduction and the risk of developing food allergy, atopic dermatitis, or childhood asthma. Limited to strong evidence (depending on the specific food studied) suggested that the risk of food allergy and atopic dermatitis did not increase by introducing allergenic foods after 4 months of age but within the first year of life, although it may prevent peanut and egg allergy.…”
Section: Introductionmentioning
confidence: 99%
“…I tråd med dette angir den norske retningslinjen (2) at alle spedbarn bør få matvarer som kan vaere allergifremkallende i løpet av det første året. Det er imidlertid ikke grunnlag for å anbefale introduksjon av potensielt allergifremkallende matvarer tidligere enn seks måneders alder (4,13,14). Med dagens kunnskapsgrunnlag er det ikke belegg for å si om introduksjon av potensielt allergifremkallende matvarer ved fire eller seks måneders alder kan forebygge utvikling av allergi.…”
Section: Allergiunclassified
“…Results from the Learning Early About Peanut Allergy trial suggested that peanut should be introduced between 4 and 11 months in infants at high risk for allergy (33). According to a recent systematic review, this practice may reduce the risk of peanut allergy, with the strongest evidence supporting a benefit to high risk infants (i.e., with severe atopic dermatitis or egg allergy) but it is also applicable to infants at lower risk (34). In addition to these findings, there is limited high quality evidence suggesting the lack of a relationship between consumption of peanut during weaning and the risk of atopic dermatitis/eczema and asthma, while not enough evidence supports the causal relationship between consuming peanut and developing allergic rhinitis at 2, 5, or 6 years of age (34).…”
Section: Complementary Feeding: Does Timing Of Food Introduction Inflmentioning
confidence: 99%
“…Previous observational studies have also investigated the effect of the timing of fish introduction on the risk of allergic diseases (40,41). A recent systematic review provided limited evidence to suggest that the introduction of fish between 3 and 8 months of life may lower the risk of atopic dermatitis/eczema (34). However, at present there is not enough evidence of a link between fish consumption and food allergy, asthma, or allergic rhinitis (42).…”
Section: Complementary Feeding: Does Timing Of Food Introduction Inflmentioning
confidence: 99%